Smart Waste Planning As An Effort To Utilize Plastic Waste Through The Making Of Paving Blocks By The Community In Pisugi District - Ayu Anggraini Tambunan; Futri Wulandari; Nepri Weya (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Plastic waste management remains a critical environmental challenge in Indonesia, particularly in remote areas like Pisugi District, Jayawijaya Regency, Mountains Papua. High plastic consumption combined with limited waste infrastructure leads to significant environmental and public health risks. This community service project applies the Smart Waste Planning concept to empower local residents by transforming plastic waste into paving blocks, a sustainable and economically valuable product. Conducted through a participatory and educational approach, the program involved field observation, socialization, hands-on technical training, mentoring, evaluation, and sustainability planning. The two-day training successfully enhanced public awareness, technical skills, and cooperation among 16 participants from district leadership and community representatives. Challenges such as limited equipment and material variation were addressed through collaborative problem-solving. The paving blocks produced demonstrate promising structural quality for light infrastructure use, opening new economic opportunities and reinforcing local environmental stewardship. Support and involvement from district government strengthened program legitimacy and sustainability prospects. This initiative integrates environmental preservation, social empowerment, and economic development, aligning with sustainable development and circular economy principles. The Smart Waste Planning model serves not only as a technical solution but as a comprehensive community empowerment strategy toward a stronger and self-reliant local society.